Estratégias de avaliação da resistência à murcha-de-ceratocystis causada por Ceratocystis fimbriata em Tectona grandis - Alexandre, Flávia Sampaio (2020)
Ceratocystis wilt caused by Ceratocystis fimbriata is one of the most important limiting factors productivity in Tectona grandis plantation. This disease has a rapidly capacity of dissemination and once the pathogen colonizes the vascular tissues of the plant, the damage is irreversible. The most efficient way to minimize the losses caused by ceratocystis wilt in tree species is by planting of resistant genotypes. But to screening and selection resistant genotypes, the pathogenicity test must carry out under controlled conditions using an inoculation standard protocol to each pathosystem. However, the lack of a standard inoculation method and evaluation of severity of ceratocystis wilt in teak, become difficult the control of the disease by genetic resistance. Another way to use genetic resistance is by systemic resistance induction mechanism (IRS) promoted by symbiotic and associative microorganisms from the rhizosphere enabling the planting of susceptible genotypes, but highly productive. Thus, the aims of the present study were to select an inoculation standard method and evaluation of severity of ceratocystis wilt in teak to select resistant genotypes under controlled conditions and to evaluate the potential of the association of beneficial rhizosphere microorganisms in systemic induction of resistance, using the arbuscular mycorrhizal fungus (AMF) Rhizophagus clarus and the rhizobacteria Bacillus subtilis. Three methods of inoculation of C. fimbriata were evaluated: (I) injection of spore suspension into the stem, (II) replacement of a piece of bark by fungus mycelium disk and (III) inoculation of spore suspension in the roots. The standard inoculation methods were evaluated on six commercial clones of teak and one isolate of Ceratocystis fimbriata used. We concluded that the method II is more efficient and quickly to screening for resistance to Ceratocystis wilt in teak. Variability for resistance between genotypes evaluated shown that is possible select resistant clones for commercial planting. The utilization of IRS by beneficial rhizosphere microorganisms shown as a promising complementary strategy to control ceratocystis wilt in teak, in susceptible clones, when B. subtilis and the FMA R. clarus were incorporated into the substrate used for cuttings production.